Processo de destilação para redução de contaminação por carbamato de etila em bebidas alcoólicas - Faria, João Bosco [UNESP]; Cavalcanti, Aline Ferreira; Mattar, Luiz do Carmo (Instituto Nacional de Propriedade Industrial (INPI), 2014)
Contamination of Brazilian sugar-cane rum by ethyl carbamate, a potentially carcinogenic substance, is considered an obstacle to export of the beverage. Copper is involved in ethyl-carbamate-formation reactions, and the replacement thereof by stainless steel in distillation equipment, with the aim of preventing the formation of said compound, results in a beverage of poor sensory quality owing to the presence of dimethyl sulphide. A reduction in the concentration of sulphurated compounds in the final product may be achieved by the placing of a copper device (Patent No. 8206688) inside the dome of a stainless-steel alembic. It is therefore appropriate to verify the efficiency of using other forms of catalysts that, in addition to reducing ethyl-carbamate levels, are able, likewise, to trigger other catalytic actions that allow the production of a distillate of good sensory quality. Silver is the noble metal most used in industry and, on account of the catalytic properties thereof, it is ideal for use as a catalyst in oxidation reactions. The subject matter of the present invention comprises a method involving the use of silver in the distillation of alcoholic beverages, such as sugar-cane rum, which reduces ethyl-carbamate contamination of the end-product.
Distillation Process for Reducing Ethyl Carbamate Contamination in Alcoholic Beverages
Processo: BR102012012855A2
Processo: WO2013177645
Número de publicação: BR102012012855 (A2)
Número de aplicação: BR20121012855